Clinical Instructors' Experience of Managing Students' Errors: A Qualitative Study. Issue 4 (July 2019) - Shahoei, Ronak; Fathi, Mohammad; Valiee, Sina
Abstract : Abstract: Given the importance of patient safety, this study aimed to explore clinical instructors' experience of managing students' errors. A qualitative approach was adopted to conduct semistructured interviews with 12 clinical nursing and midwifery instructors. Three main categories emerged: prevention (orienting, review of the knowledge, repeating procedure by instructor, checking steps prior to performing procedure, and reminding), action (correcting, monitoring and follow-up, and informing), and feedback (cause analysis, notifying, and affecting assessment). Patient safety and error management programs should be included in the nursing curriculum and nursing education.